Pengaruh Pemberian Pupuk NPK dan Media Arang Sekam Terhadap Pertumbuhan dan Produksi Bawang Merah (Allium cepa L.) - Mitason, Deka; Sari, Wilna; Putri, Santi Diana; Fevria, Resti; Marni, Yunis (JURNAL AGROPLASMA, 2024)
Shallots are known as a type of spice for food flavoring and also as a traditional medicine whose benefits have been felt by the wider community. The production of shallots in Sijunjung Regency has not shown optimal results even though NPK fertilizers have been used. To overcome this, it is necessary to add organic fertilizers such as husk charcoal. This study aims to determine the effect of the growth and production of Allium cepa (L.) shallots on the combination of applying npk fertilizer and husk charcoal.The research was in the form of an experiment using a complete randomized design (RAL) with five treatments and four replicates. P0 treatment (NPK 0g/polybag + husk charcoal 0g/polybag), P1 treatment (NPK 1.25g/polybag x 8 + husk charcoal 80g/polybag), P2 treatment (NPK 1.30g/polybag x 8 + husk charcoal 90g/polybag), P3 treatment (NPK 1.35g/polybag x 8 + husk charcoal 100g/polybag), P4 treatment (NPK 1.40g/polybag x 8 + husk charcoal 110g/polybag). The variables observed were plant height, number of leaves per clump, number of tubers per clump, wet weight and dry weight. Furthermore, the data was analyzed using a variety of fingerprint analysis followed by a DMRT test with a level of 5% on data that had a real effect. The results showed that the combination of NPK fertilizer and husk charcoal had a real effect on the number of leaves per clump (P <0.05) and had no real effect on plant height, number of tubers per clump, wet weight and dry weight. The P4 treatment produced the highest number of leaves (34.50 leaves), while the highest number of bulbs was also achieved by the same treatment with an average of 8.75 bulbs per clump. The conclusion of the study results is Overall, the application of NPK and husk charcoal shows the potential for an increase in the number of leaves, but it is not significant in other aspects. Keyword: shallots, husk charcoal, NPK, growth, production